Research of Electronic Structure in NdVO3 and HoVO3 Oxides: X-ray Electron Spectrum and Ab Initio Calculation of Band Structure - Uvarov, V.M.; Uvarov, M.V.; Melnik, M.P. (Ukrainian Journal of Physics, 2022)
Complex researches of the electron structure and magnetic properties of NdVO3 and HoVO3 oxides have been carried out with the use of the X-ray electron spectroscopy and ab initio numerical calculations. Data have been obtained concerning the distributions of total and partial electron densities of states in the valence and conduction bands, the charge and spin states of atoms, the mechanism of chemical bond formation, and the band gap in the energy spectra of the oxides under consideration.